Corner office [videorecording (DVD)] - Kupper, Ted; Hamm, Jon, 1971-; Pudi, Danny; Heyerdahl, Christopher; Gadon, Sarah, 1987-; Karlsson, Jonas, 1971- (Lionsgate, 2023)
As The Authority's newest employee, Orson finds it difficult to connect with his enigmatic desk mate, Rakesh, or any of his other colleagues. His alienation deepens when he discovers a room he's told doesn't exist, a place that unleashes his true potential, leading to an ascent up the corporate ladder. Buoyed by his newfound confidence, Orson invites a receptionist into his sanctuary, sparking a climactic clash between the corporate world's harsh realities and his wild fantasies.